Austromorium, a new myrmicine ant genus from Australia (Hymenoptera: Formicidae) - Shattuck, Steven O. (Zootaxa, 2009)
The myrmicine ant genus Austromorium is described for two Australian endemic species. One species has been known for some time but its taxonomic placement has been unclear while the second species is newly described. They are thought to be related to Lordomyrma and Austromorium is tentatively placed within the tribe Stenammini. These are ground-nesting ants although little else is known of their biology. While one species is widespread across semi-arid southern Australia the other is restricted to a narrow band of coastal south-western Western Australia.